Characteristics of the GlnH and GlnX Signal Transduction Proteins Controlling PknG-Mediated Phosphorylation of OdhI and 2-Oxoglutarate Dehydrogenase Activity in Corynebacterium glutamicum - Lea Sundermeyer; Graziella Bosco; Srushti Gujar; Melanie Brocker; Meike Baumgart; Dieter Willbold; Oliver H. Weiergräber; Marco Bellinzoni; Michael Bott (Microbiology Spectrum, 2022)
ABSTRACT In Corynebacterium glutamicum the protein kinase PknG phosphorylates OdhI and thereby abolishes the inhibition of 2-oxoglutarate dehydrogenase activity by unphosphorylated OdhI. Our previous studies suggested that PknG activity is controlled by the periplasmic binding protein GlnH and the transmembrane protein GlnX, because ΔglnH and ΔglnX mutants showed a growth defect on glutamine similar to that of a ΔpknG mutant. We have now confirmed the involvement of GlnH and GlnX in the control of OdhI phosphorylation by analyzing the OdhI phosphorylation status and glutamate secretion in ΔglnH and ΔglnX mutants and by characterizing ΔglnX suppressor mutants. We provide evidence for GlnH being a lipoprotein and show by isothermal titration calorimetry that it binds l-aspartate and l-glutamate with moderate to low affinity, but not l-glutamine, l-asparagine, or 2-oxoglutarate. Based on a structural comparison with GlnH of Mycobacterium tuberculosis, two residues critical for the binding affinity were identified and verified. The predicted GlnX topology with four transmembrane segments and two periplasmic domains was confirmed by PhoA and LacZ fusions. A structural model of GlnX suggested that, with the exception of a poorly ordered N-terminal region, the entire protein is composed of α-helices and small loops or linkers, and it revealed similarities to other bacterial transmembrane receptors. Our results suggest that the GlnH-GlnX-PknG-OdhI-OdhA signal transduction cascade serves to adapt the flux of 2-oxoglutarate between ammonium assimilation via glutamate dehydrogenase and energy generation via the tricarboxylic acid (TCA) cycle to the availability of the amino group donors l-glutamate and l-aspartate in the environment. IMPORTANCE Actinobacteria comprise a large number of species playing important roles in biotechnology and medicine, such as Corynebacterium glutamicum, the major industrial amino acid producer, and Mycobacterium tuberculosis, the pathogen causing tuberculosis. Many actinobacteria use a signal transduction process in which the phosphorylation status of OdhI (corynebacteria) or GarA (mycobacteria) regulates the carbon flux at the 2-oxoglutarate node. Inhibition of 2-oxoglutarate dehydrogenase by unphosphorylated OdhI shifts the flux of 2-oxoglutarate from the TCA cycle toward glutamate formation and, thus, ammonium assimilation. Phosphorylation of OdhI/GarA is catalyzed by the protein kinase PknG, whose activity was proposed to be controlled by the periplasmic binding protein GlnH and the transmembrane protein GlnX. In this study, we combined genetic, biochemical, and structural modeling approaches to characterize GlnH and GlnX of C. glutamicum and confirm their roles in the GlnH-GlnX-PknG-OdhI-OdhA signal transduction cascade. These findings are relevant also to other Actinobacteria employing a similar control process.